Efek Atribut Chatbots Pada Hubungan Pelanggan Dengan Merek: PLS-SEM dan Analisis Peta Kepentingan-Kinerja Terhadap E-Commerce Shopee dan Tokopedia di Jakarta - Hutomo, Kayla Nirandra Alifia; Sugama, Nuresa Ibnu; Carolina, Elisabeth Christine; Riorini, Sri Vandayuli (Peneliti.net, 2024)
This research aims to analyze the effect that customer satisfaction gained from interaction with a chatbot can have on improving and empowering the overall quality of brand relationships. Therefore, this study will discuss about